Assessment of willingness-to-pay for Aflasafe KE01, a native biological control product for aflatoxin management in Kenya - Migwi, B.; Mutegi, C.; Mburu, J.; Wagacha, J.; Cotty, P.J.; Bandyopadhyay, R.; Manyong, Victor M. (Informa UK Limited, 2020)
Contamination of key staples with aflatoxins compromises the quality of food and feed, impedes trade, and negatively affects the health of consumers whereas acute exposure can be fatal. This study used the Contingent Valuation Method (CVM) on a sample of 480 farmers in counties prone to aflatoxin contamination to assess the willingness to pay (WTP) by farmers for Aflasafe KE01, a promising biological control product for the management of aflatoxin contamination of key staples in Kenya, compare its cost with that of a similar product in use in Nigeria, and determine factors likely to affect its adoption. Four hundred and eighty households from four counties identified as aflatoxin hotspots in Kenya were purposively selected and interviewed using a semi-structured questionnaire. The mean WTP per kilogram of Aflasafe KE01, using Contingent Valuation Method in the four counties ranged from Kenya Shillings (Ksh) 113 to 152/kg compared to a cost of Ksh. 130/kg, the price of a similar product, AflasafeTM, in Nigeria. Factors that positively influenced farmers’ WTP included information from crop extension services and access to credit. To facilitate the adoption of Aflasafe KE01 or any other biocontrol product in Kenya and elsewhere, there is a need for increased education efforts through extension services to farmers about aflatoxins. Strategies to ensure that the biocontrol product is integrated into the credit scheme of the technological packages to farmers need to be considered.